Answer:
y=-5x+16
Step-by-step explanation:
Plug in the slope and point coordinates into point-slope form (attached in image)
(y-6)=-5(x-2)
1) Distribute -5 to x and -2:
y-6=-5x+10
2) Add 6 to both sides:
y=-5x+16
Answer: (n+5)x(n+1)
Step-by-step explanation:
1. Write 6n as a sum
2. Factor out n form the expression
3. Factor out n+5 from the expression
(n+5)x(n+1)
tiene que sacar la raiz nena
<em>the remainder is </em><em>- 1</em>
- Step-by-step explanation:
<em>when (x ³ - 7x + 5) is divided by (x + 3) the remindeer is f( -3 )</em>
<em>x + 3 = 0 => x = - 3</em>
<em>f(-3) = (-3)³ - 7(-3) + 5</em>
<em>= - 27 + 21 + 5</em>
<em>= - 1</em>
<em />